Physical exercise and academic performance among students in the medical field at Jordanian Universities - Ahlam J. Alhemedi; Sawsan Abuhammad; Thekraiat Majed A.L. Quran; Omar Khasawneh; Motaz Al-Yafeai; Mohammed Al-Wazeer (PLoS ONE, 2026)
Background The literature emphasizes multiple factors that affect academic performance, including emotional and physical well-being, motivation, and physical exercise. University students, especially medical students, usually lack time and experience high levels of stress, leading to neglect of a healthy lifestyle. This study aimed to assess the association between physical activity patterns and academic performance (cumulative grade point average (cGPA)) among medical students at Jordanian universities. Methods This is an online survey study that was conducted in Jordan between 28/12/2023 and 30/07/2025. A multivariate logistic regression analysis was performed to identify sociodemographic and physical activity items associated with academic performance, while sociodemographic characteristics were analyzed to predict the probability of engaging in physical activities among participating students. Results A total of 1,209 university students participated in this study. Around 54.8% reported engaging in physical activity. Vigorous exercises such as running or football were practiced by 61.8%, and moderate activities such as brisk walking or swimming by 74.8%. Nearly half of the participants (45.9%) had been exercising for over a year, and 42.7% exercised more than 2.5 hours weekly. The main motivations for physical activity included maintaining health (39.9%) and stress relief (31.8%), while barriers included a lack of time (33.1%) and energy (26.9%). Students aged 22–24 were significantly less likely to have cGPA > 3.5 compared to those aged 18–21 (adjusted odds ratio (aOR) = 0.6, 95% confidence interval (CI): 0.4–0.9; p = 0.021). Additionally, non-Jordanian students had a lower likelihood of achieving a cGPA > 3.5 compared to Jordanian students (aOR = 0.3; 95% CI: 0.2–0.5; p < 0.001). Conclusion In this study sample, medical students exercise moderately. Health improvement and stress relief were the main motivators, whereas a lack of time and energy were barriers. Significant cGPA variances were seen according to age, university, and nationality, revealing sociocultural and institutional impacts within this study population. Although physical activity was not significantly associated with academic performance, females showed lower odds of participating in physical activity, highlighting the importance of promoting physical activity among women to improve overall student health and well-being.